Penguatan branding olahan jamur sawit crispy melalui pendekatan partisipatif di Dusun Sentimok - Muhammad Syahnanda Irgi Pangestu; Artika Yandani; Sanggar Tribuana Tungga Dewi; Lola Lola (ABDIMASY: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Sentimok Hamlet, located in the Indonesia–Malaysia border region of Bengkayang Regency, possesses local potential in the form of mushrooms cultivated on oil palm substrates, which can be developed into a value-added product, namely crispy oil palm mushroom snacks. However, product development has been constrained by limitations in branding, brand identity, and marketing strategies, resulting in relatively low product competitiveness. This community service program aimed to strengthen community capacity in developing product branding to enhance product value and support local economic independence. The program employed a participatory approach with a quantitative descriptive design through seminars, branding workshops, and evaluations using a Likert-scale questionnaire administered to 45 participants. The evaluation results indicated positive outcomes, with all indicators categorized as high to very high. The highest mean score was recorded for the program benefits and impacts aspect (4.54), followed by program relevance (4.47), improvement in participants’ knowledge and skills (4.17), and understanding of branding and product value enhancement (4.12).